The Impact of Construction Activities Near the Gulf: The Likelihood of Construction Materials Effect, ERA and Sustainable Development - Motaleb, Omayma; Hijah, Esraa (International Journal of Membrane Science and Technology, 2023)
The environmental risks associated with construction activities are being monitored, especially given the global construction boom, in which the United Arab Emirates is a major participant. Construction activities near Gulf water cause variations in the ecosystem, yet whilst the Environmental Protection Agency (EPA) has given much attention to environmental risks resulting from construction material during construction activities to streams and rivers, there has been limited exploration of those risks in the Gulf. This research paper aims to identify the best practices in Environmental Risk Assessment (ERA) in order to contribute towards the achievement of sustainable development. Specifically, the objective is to determine the relationship between the parameters of water quality (turbidity and pH) that affect the ecosystem during construction activities in the hot summer and to frame effective ERA, to pursue this aim, 32 water samples were collected from the Gulf water in two locations; the first adjacent by 12 m to the Gulf and at a 500 m distance from the second, inactive location in Abu Dhabi city, UAE. All these water samples were taken during the peak time of construction activities, and after six hours of no activities, taking into consideration the weather conditions. Samples were tested in the environmental laboratory within 24 hours. The temperature is particularly considered to predict future levels of variation and consider risks that will affect such areas and seasons. The results indicate that a maximum turbidity level of 25.2 NTU (Nephelometric Turbidity Units) was noticed when the temperature was 43°C and pH 5.9 at the active construction. Hence a strong relationship between turbidity, pH, and temperature and their impacts on the water quality of the Gulf during construction activities is revealed. Outcomes are promising in effective risk management for sustainable development of the Gulf ecosystem during construction activities. The study demonstrates the need for a successful risk management framework to focus on the construction material management treatment that can decrease turbidity and adjust pH in the Gulf water near active construction. In addition, managing statistics of the communities residing near the Gulf and re-evaluating environmental risks are crucial.